TEACHING READING COMPREHENSION THROUGH THE INTERACTIVE TECHNIQUE (A QUASI-EXPERIMENTAL REASEARCH AT THE SMPN 1 BENGKULU CITY) - Aleti Monarisa (Islamic State Institute of Bengkulu (IAIN) Bengkulu, 2015)
Teaching reading comprehension through the interactive technique (a quasi-experimental research at the smpn 1 bengkulu city). The objective of this research was to find out whether the Interactive technique could improve students’ reading comprehension. This was a quasi-experimental research. The population of this research was the eighth grade students of SLTP Negeri 1 Kota Bengkulu which consisted of 193 students. The sample of this research was the class VIII.2 (34 students) as the experimental group and the VIII.3 (40 students) as the control group. The instrument was a reading comprehension test, which consisted of 40 items. Before the pre-test was given, it was tried out to the students of the same level. The result was t-count in the pre-test was smaller than t-table (1.26 < 2.042). This indicated that the groups were of equal ability. For the post-test, in contrast, the t-count was greater than t- table (2.7 > 2.042). This indicated that the interactive technique could improve students’ reading comprehension